Euterpe oleracea extract inhibits tumorigenesis effect of the chemical carcinogen DMBA in breast experimental cancer - Jéssica Alessandra-Perini; Jamila Alessandra Perini; Karina Cristina Rodrigues-Baptista; Roberto Soares de Moura; Antonio Palumbo Junior; Thiago Alves dos Santos; Pergentino José Cunha Souza; Luiz Eurico Nasciutti; Daniel Escorsim Machado (BMC, 2018)
Abstract Background Among the processes involved in the breast tumor microenvironment, angiogenesis and inflammation play a central role, and the main factors of these processes are the vascular endothelial growth factor (VEGF), cyclooxygenase 2 (COX-2) and macrophages. Recently, the extract of Euterpe oleracea (açaí), a fruit that is widely found in the Amazon region, already showed antitumorigenic effects in vitro in human breast cancer cell lines. The present study aimed to investigate the effect of açaí on breast cancer using a chemically DMBA (7,12-dimethylbenzanthracene) experimental model. Methods One day after initiation of treatment with açaí, mammary carcinogenesis was induced in female Wistar rats using a subcutaneous injection of 25 mg/kg of DMBA in the mammary gland. Forty rats were randomized into two groups: treated with 200 mg/kg of either açaí extract or vehicle, via gastric tube for 16 consecutive weeks. After treatment, the tumor was collected for macroscopic, histological and immunohistochemical (VEGF, vascular endothelial growth factor receptor 2 -VEGFR-2, COX-2 and matrix metalloproteinase -MMP-9) analyses; peritoneal fluid was subjected to flow cytometry (F4-80/MAC-2+) and ELISA immunoassay (VEGF, prostaglandin E2 -PGE2 and interleukin-10 -IL-10). Heart, liver and kidney samples were collected for histological analysis. Results After 16 weeks of induction, the mammary carcinoma was confirmed by macroscopic and histological evaluation. Survival analysis indicates that açaí increased the survival (P = .0002, long-rank test) and reduced the deaths number (P = .0036, Chi-square test). Açaí treatment decreased the number of inflammatory cells and macrophage positive cells (Mac-2 + F4-80+), as well as promoting a reduction in immunostaining of VEGF, VEGFR-2 and COX-2. The açaí group also exhibited lower concentrations of PGE2, VEGF and IL-10 compared to the control. The histopathological results of the liver and kidneys showed protective effect of açaí, since in the control group, there was an increase in fibrosis, atypical cells and hemorrhagic microenvironment. Conclusion The results of this study demonstrated the antiangiogenic and anti-inflammatory potential of açaí, like due to the decreases of the number of activated macrophages, resulting in the inhibition of DMBA carcinogenicity in breast cancer.